Assessing the adequacy of a protected area network in conserving a wide‐ranging apex predator: The case for tiger (Panthera tigris) conservation in Bhutan - Phuntsho Thinley; Rajanathan Rajaratnam; Stephen J. Morreale; James P. Lassoie (Conservation Science and Practice, 2021)
Abstract Protected area networks (PAN) are essential for conserving wide‐ranging apex predators but their adequacy in species protection has rarely been assessed. Here, we assess the adequacy of Bhutan's PAN in conserving and providing connectivity to the endangered tiger (Panthera tigris). We determine the current extent of tiger habitat, predict new suitable habitat, identify potential corridors, and empirically estimate the range of tiger numbers that Bhutan can spatially support. We use two spatial models with different approaches to ascertain current tiger distribution and predict new suitable tiger areas: (a) an expert model based on tiger ecology and (b) an observation model from observed tiger distribution. The expert model identified more suitable tiger areas (32,887 km2) over the observation model (29,962 km2), with the PAN encompassing 46% and 45% of predicted suitable areas, respectively. Vast suitable tiger habitat remains unprotected. Based on our estimates of total suitable habitats, Bhutan can spatially support 138–151 tigers compared to the current estimate of 103, thereby precluding a doubling in tiger numbers. To ensure adequate protection of tigers in Bhutan, we recommend readjusting and/or expanding existing PAN boundaries, including the designation of new corridors, protecting habitats, and conserving prey populations.